Influence of the Multiple Layers Application and the Heating of Silane on the Bond Strength between Lithium Disilicate Ceramics and Resinous Cement - Silva, Uriel Paulo Coelho; Maia, Andréa Peixoto; Silva, Isaias Donizeti; Miranda, Milton Edson; Brandt, William Cunha (European Journal of Dentistry, 2021)
Objective This study aimed to evaluate the bond strength between lithium disilicate ceramic and resinous cement when silane (Prosil, FGM) was applied in different amounts of layers under heating or not.Materials and Methods Sixty IPS E-max CAD ceramic (Ivoclar) was used. They were conditioned with 10% hydrofluoric acid for 20 seconds. The samples were distributed in six groups (n = 10): 1Sil, 1 layer of silane without heating; 1SilAq, 1 layer of silane with heating; 2Sil, 2 layers without heating; 2SilAq, 2 layers with heating; 3Sil, 3 layers without heating; and 3SilAq, 3 layers with heating. After each layer, a jet of cold air was applied for 20 seconds in groups 1Sil, 2Sil, 3Sil, and jet of hot air (50°C) in groups 1SilAq, 2SilAq, and 3SilAq. Subsequently, an adhesive layer was applied, and fourcylinders were made on the ceramic with a resin cement AllCemVeneer and photoactivated for 20 seconds. The samples were stored at 37°C for 24 hours and analyzed to the microshear test at EMIC.Statistical Analysis Data were submitted to ANOVA and Tukey’s test (α = 0.05).Results The results showed that there was no statistical interaction between the factors studied. The “heating” factor was not statistically significant; however, the “silane layers” factor showed differences between groups. The analysis of the results showed that the use of one (66%) or two layers (67%) of silane regardless of heating, produced higher values of bond strength, when compared with the group of three layers (62%).Conclusion The use of silane with one or two layers provided a greater bond strength between lithium disilicate ceramic and resinous cement and that the heating did not influence the results.
Keywords: silanes; ceramics; cementation